2013
DOI: 10.1038/nrmicro3028
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of metals: mechanisms, molecular targets and applications

Abstract: Metals have been used as antimicrobial agents since antiquity, but throughout most of history their modes of action have remained unclear. Recent studies indicate that different metals cause discrete and distinct types of injuries to microbial cells as a result of oxidative stress, protein dysfunction or membrane damage. Here, we describe the chemical and toxicological principles that underlie the antimicrobial activity of metals and discuss the preferences of metal atoms for specific microbial targets. Interd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
1,682
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,212 publications
(1,715 citation statements)
references
References 164 publications
15
1,682
0
18
Order By: Relevance
“…In a study by Hardes et al [15], however, no local or systemic side-effects were reported after placement of Ag coated megaprostheses in 20 patients, although Ag blood levels exceeded 55 ppb, and 1600 ppb was detected in nearby tissue. As antibiotic resistance is spreading among pathogens, alternatives are sorely needed and a growing body of work is now dedicated to studying metal-based antimicrobials to treat infections [55].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Hardes et al [15], however, no local or systemic side-effects were reported after placement of Ag coated megaprostheses in 20 patients, although Ag blood levels exceeded 55 ppb, and 1600 ppb was detected in nearby tissue. As antibiotic resistance is spreading among pathogens, alternatives are sorely needed and a growing body of work is now dedicated to studying metal-based antimicrobials to treat infections [55].…”
Section: Discussionmentioning
confidence: 99%
“…Several articles have also been written to explain mechanistically the mode of action of silver nanoparticles [15][16][17][18][19]. However, most work focused on the empirical observations of effects that lead to the eradication of the target microbes, and very little rationalization on the general antimicrobial pathways was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Only general trends will thus be described. More information can be found in excellent reviews on the subject [15][16][17][18][19]. Additionally, toxicity issues for humans (systemic and at the cellular level) are topics of primary concern related to Ag NPs, but will not be developed here.…”
Section: Introductionmentioning
confidence: 99%
“…However, selection of in vitro models is often arbitrary, as well as the chosen nanoparticles and exposure conditions. Silver nanoparticles (AgNPs) are interesting for a mechanistic evaluation of in vitro tests because their mechanism of action is suggested to depend on both Ag + and NPs (Ivask et al, 2014;Lemire et al, 2013). In suspension, AgNPs have been described to release ions (Kittler et al, 2010), which strongly contribute to the biological activity of AgNPs in vitro and in vivo (Bouwmeester et al, 2011;Foldbjerg et al, 2012;van der Zande et al, 2012).…”
Section: Introductionmentioning
confidence: 99%